2015
DOI: 10.15376/biores.10.4.7386-7404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Treatments on the Physical Properties of Non-woven Jute/PLA Biocomposites

Abstract: Biocomposites based on poly(L-lactic acid) (PLA) and non-woven jute fabrics (NWJF) were fabricated by sandwiching non-woven jute mat between PLA sheets. First, composites were fabricated with various weight proportions of jute fabric (5, 10, 20, and 30 wt.%) with the PLA matrix, and the effect of fabric loading on their mechanical properties was investigated. Higher mechanical properties were found at 10 wt.% fabricloaded composite. The results show that the tensile, flexural, and impact strengths were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…The use of silane coupling agents, grafing by bifunctional monomers and the plasma treatment of the fiber surfaces are the most common techniques of interface modification of composites (Pothan et al 2002;Khan et al 2009;Khan et al 2013a;El-Sabbagh 2014;Khan et al 2015a;Khan et al 2015b). In the present investigation, to improve the fiber matrix interaction, jute fiber surface have been modified by NaOH, dicumyl peroxide, potassium dicromate, and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of silane coupling agents, grafing by bifunctional monomers and the plasma treatment of the fiber surfaces are the most common techniques of interface modification of composites (Pothan et al 2002;Khan et al 2009;Khan et al 2013a;El-Sabbagh 2014;Khan et al 2015a;Khan et al 2015b). In the present investigation, to improve the fiber matrix interaction, jute fiber surface have been modified by NaOH, dicumyl peroxide, potassium dicromate, and hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 92%
“…The NaOH treated fiber were treated by 0.055 w/v% K 2 Cr 2 O 7 solution maintained the fiber to liquor ratio 1: 15 for 30 min at 60°C with occasionally added few drops of H 2 SO 4. Then the fiber was washed by distilled water and dried in air (Khan et al 2015b).…”
Section: Fiber Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile and bending strengths of the developed composites were improved by surface modifications, with alkali treatment and cyanoethylation producing the best mechanical properties. Alkali, acetic anhydride, acrylonitrile, KMnO4, diphenylmethane disocyanate, and benzoyl chloride treatments were used on jute fiber mat reinforced PLA composites (Khan et al 2015); the alkalibenzoylated treated composite showed higher tensile, flexural, and impact strength than the composite made from untreated fibers. Similarly, Rahman et al (2015) prepared a photo-catalytic fiber by modifying the surface of jute fiber with a Bi2O3/TiO2 composite.…”
Section: Introductionmentioning
confidence: 99%
“…Combining natural plant fiber (wood, bamboo, sisal, jute, rice hull, etc. ) instead of synthetic fiber (glass or carbon fiber) with recycled thermoplastic polymers is receiving more attention, due to the many advantages of natural fiber: enormous quantity, high specific strength and modulus, environmentally friendly characteristics, low cost, good machineability, and recyclability (Segerholm et al 2012;Kaewkuk et al 2013;Petchwattana and Covavisaruch 2013;Cavdar et al 2014;Xue et al 2014;Khan et al 2015).…”
Section: Introductionmentioning
confidence: 99%